St. Stephen's Church on Hanover Street, ca. 1975 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southeast of St. Stephen's Church, located on Hanover Street between Harris Street to the north and Clark Street to the south. The facade of the church faces west. Automobiles line Hanover and Harris Streets, and pedestrians are visible in front of the entrance to the church. A tall street lamp is located on the southeast corner of Harris and Hanover Streets. 8 1/16 x 7 1/16, 9 1/2 x 8 overall Photographs